Utilization of thermoplastic polymer waste in blends with petroleum bitumen fractions - Zieliński, J.; Gurdzińska, E.; Osowiecka, B.; Brzozowska, T.; Ciesińska, W. (Polimery, 2010)
New polymer-bitumen compositions based on thermoplastic polymers and heavy fractions from crude-oil processing have been developed. The parameters for the preparation of homogeneous and stable composites (Table 3) containing particular types of thermoplastic wastes of PE, PP, PS, PC (Table 1) and secondary bitumen oils such as clarified, pirolytic, used engine oils or furfurol extract (Table 2) have also been established. The obtained dual-content compositions underwent comprehensive thermomechanical and Theological tests in order to determine their applicability as binding agents in consumer products (Table 4, Figs. 1, 2). A preparation method developed for application of the new consumer materials for use as the joint sealants, seal mastics, asphalt primer solutions and asphalt-polymer adhesives was established and a full range of tests performed in accordance with current regulations (Tables 5-9, Figs. 3,4) performed on them. The possibility of utilizing the waste polymers in the secondary bitumen environment in extreme conditions (Table 10, Fig. 5) was evaluated. The obtained thermolysis products can be used in the bri-quetting of solid fuels, modification of the poperties of petroleum asphalt and the preparation of sealing components for the construction industry.